The effect of teacher professional certification and work motivation on the performance of elementary school teachers in the Kempas district, Indragiri Hilir regency - Udi Priyono; Isjoni; Bunari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
One of the determinants of educational success is teacher performance. Teachers are professional educators with essential duties, functions, and roles in achieving school goals. However, in reality, based on the results of pre-research with several principals and teachers of state elementary schools in Kempas Indragiri Hilir District, there are several phenomena where some teachers still experience problems and obstacles in carrying out their professional duties. This research aims to determine the effect of teacher professional certification on the performance of public elementary school teachers in Kempas Indragiri Hilir District, to determine the influence of teacher work motivation on the performance of public elementary school teachers in Kempas Indragiri Hilir District, and to determine the effect of teacher professional certification and teacher work motivation on their performance in elementary schools. Negeri Se Kecamatan Kempas Indragiri Hilir. This research uses an associative design with a quantitative approach. Data collection techniques in this research used questionnaires and documentation. Based on the research results, it is known that there is a significant and positive influence of professional certification on teacher performance in State Elementary Schools in Kempas District, Indragiri Hilir Regency, which is shown by the t-test that the sig value is 0.000. If the sig value is smaller than the probability value of 0.05 or 0.000 < 0.05, then H1 is accepted, and H0 is rejected. So, it can be concluded that work motivation and teacher professional certification positively influence teacher performance in State Elementary Schools in Kempas District, Indragiri Hilir Regency.